EDUKASI MENINGKATKAN PENGETAHUAN IBU BALITA STUNTING TENTANG STUNTING DAN RESPONSIVE FEEDING - Yossy Utario; Misniarti Misniarti; Yanti Sutriyanti (Jurnal Ilmu Keperawatan Anak, 2023)
Stunting is a condition where toddlers have a length or height that is less than their age. One of the causes of stunting is ineffective feeding practices. Responsive feeding is the ability of caregivers to feed children actively and responsively. This study aimed to determine the effect of education on stunting and responsive feeding on mother's knowledge of stunting. This research method used a pre-experimental design with one group pretest and posttest design. The sample in this study used purposive sampling, with the number of respondents being 34 mothers of stunting toddlers in 3 working areas of public health centers in Rejang Lebong Regency, Bengkulu Province. The interventions provided included education about stunting and responsive feeding using booklets. Data collection using a knowledge questionnaire instrument about stunting and responsive feeding. Data analysis used paired t test and Wilcoxon test. The results showed that there was a significant difference in maternal knowledge about stunting and responsive feeding before and after receiving educational intervention with a P value of 0.000 (<0.05). It can be concluded that the booklet media has an effect on increasing the knowledge of mothers of stunting toddlers.